ZnxCd1-x (O) Thin Film Nanorods for PV Applications - Mohamad, Souad A.; Mushtaq, Umer (2013)
ZnxCd1-x (O) nanorods (NRs) thin films were deposited on ITO glass substrate by using a single step controlled electrodeposition process. Thin films of crystalline nature with zinc and cadmium concentration changing from 10% - 90% were electrodeposited onto ITO conductive glass substrates. XRD analysis confirms a hexagonal wurtzite structure having grain size 37 nm. The FESEM images of ZnxCd1-x (O) shows that hexagonal nanorods were first time synthesized via electrodeposition technique at temperature of 90 oC and the size of each regular plane of hexagonal nanorods is about 63nm. The Cd content of ZnxCd1-xO nanorods was as high as (about) 16.7 at% which as calculated by EDX. Remarkably, the ultra-violet (UV) near-band-edge (NBE) emission was red-shifted from 3.21 eV to 3.04 eV due to the direct modulation of band gap caused by Cd substitution, revealed by UV visible spectroscopy. Temperature is deemed as a key parameter for the formation of different morphologies of ZnxCd1-x (O) nanostructures. Finally, ZnxCd1-xO hexagonal nanorods thin film is used as one electrode in photovoltaic cells to produce energy by absorbing the energy from the sun, this single junction cells have been put forward as a potential low-cost alternative to the widely used solar cells. However, the cost effectiveness is due to the ZnxCd1-xO nanorods electrode. Copyright © IJNST, all rights reserved.